(untitled) (Ustozlar uchun, 2026)
Authentic assessment has become an essential component of modern education, especially in language teaching. It focuses on evaluating learners’ real-life skills and competencies rather than their ability to memorize information. This article explores the concept of authentic assessment, its principles, advantages, and challenges in the educational process. It also discusses various types of authentic assessment such as portfolios, projects, presentations, and real-world tasks. The role of teachers in designing effective authentic assessment tools is highlighted, along with practical strategies for classroom implementation. The study emphasizes that authentic assessment promotes critical thinking, creativity, and learner autonomy. It prepares students for real-life communication and professional situations, making education more meaningful and practical.